Výsledky multimodální lécby glioblastoma multiforme: Konsekutivní série 86 pacientů diagnostikovaných v letech 2003-2009 - Lakomý, R; Fadrus, P; Slampa, P; Svoboda, T; Kren, L; Lzicarová, E; Belanová, R; Siková, I; Poprach, A; Schneiderová, M; Procházková, M; Sána, J; et al. (Klinicka onkologie, 2011)
BACKGROUNDS: Glioblastoma multiforme is the most common malignant primary tumor of the brain in adults. Standard therapy consists in maximal surgical resection and adjuvant concurrent chemoradiotherapy and adjuvant therapy with temozolomid. This approach improves survival in comparison with postsurgical radiotherapy alone. PATIENTS AND METHODS: Consecutive patients with histologically confirmed glioblastoma multiforme in the period from January 2003 to December 2009 underwent postoperative radiotherapy (1.8-2.0 Gy/d, total of 60 Gy) plus concurrent daily chemotherapy (temozolomide 75 mg/m2/d), followed by 6 cycles of temozolomide (150 to 200 mg/m2 for 5 days, every 28 days) and were analyzed retrospectively. The primary end point was to describe the correlation between known clinical factors, treatment and progression free survival (PFS) and overall survival (OS). We assessed the toxicity and safety of the chemoradiotherapy. RESULTS: Eighty-six patients (median age, 56 years; 60% male) were included. Most of them (> 80%) were of performance status (PS) 0-1 at the beginning of chemoradiotherapy. Total macroscopic resection was performed in 20% of the patients, subtotal in 65%, partial in 9%, and just biopsy in 6%. Median PFS was 7.0 months (2.0-35.5), median OS was 13.0 months (2.5-70). Postoperative performance status (PS), the extent of resection, and administration of planned treatment without reduction had statistically significant influences on PFS and OS. Median PFS and OS were 22.0, 7.0 and 6.0 months for PFS (p = 0.0018) in patients with PS O, 1 and 2 respectively and 32.0, 13.0 and 9.0 months for OS (p = 0.0023). Patients with total removal of tumor had longer PFS (14.0 vs 6.0 months, HR = 0.5688; p = 0.0301) and OS (23.0 vs 12.0 months, HR 0.4977; p = 0.0093), as did patients without dose reduction of radiotherapy and/or chemotherapy. Patients with radiotherapy dose of over 54 Gy had PFS 8.0 vs 3.0 months (HR = 0.3313; p = 0.0001) and OS 15.0 vs 5.0 months (HR = 0.1730; p < 0.0001). Similarly, treatment with concurrent chemotherapy for more than 40 days was also important: PFS 8.0 vs 5.0 months (HR = 0.5300; p = 0.0023) and OS 17.0 vs 9.5 months (HR = 0.5943; p = 0.0175). Age, gender and position of tumor had no significant influence. Treatment-related hematology toxicity grades 3 and 4 occurred relatively often: thrombocytopenia (9%), leukopenia (6%), neutropenia (6%) and lymphopenia (25%). Thrombo-embolic events were dominant in non-hematology toxicity. Serious toxicity occurred mainly in the subgroup of patients with PS 2. Treatment of progression was useful in selected patients. Second surgery was of the most benefit (OS 24.0 vs 12.5 months, HR = 0.5325; p = 0.0111). CONCLUSION: Postoperative performance status, extent of resection, successful administration of the majority of planned concurrent chemoradiotherapy and possibility of surgical treatment at the time of recurrence correlate with better prognosis for our patients with glioblastoma. Our experience indicates that performance status should be the main factor in decisions about treatment intensity. Treatment of malignant glioma requires a multidisciplinary team.
Keywords: dospělí; Female; kombinovaná terapie; Adult; mladý dospělý; ženské pohlaví; nádory mozku; lidé; Karnofského skóre; míra přežití; glioblastom; Glioblastoma; Male; Combined Modality Therapy; Aged; Young Adult; Brain Neoplasms; Karnofsky Performance Status; Survival Rate; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans